Editorial - Balaguera Lopez, Helber Enrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
I would like to begin this note by presenting important news for the Journal and the scientific community. After participating in the "Call for indexation of specialized scientific journals in Colombia – Publindex 2020", our Journal was awarded the category B by the Ministry of Science, Technology, and Innovation for the year 2021. I publicly express my gratitude to the publishing entities, the Colombian Society of Horticultural Sciences (SCCH) and the Universidad Pedagógica y Tecnológica de Colombia (UPTC), the editorial team, our authors, reviewers, and readers. This recognition continues to maintain us as one of the best journals in the area in the country.